Identification of Nonylphenol and Glucolipid Metabolism-Related Proteins in the Serum of Type 2 Diabetes Patients - Luo YA; Yu JIE; Yang MENGXUE; Wang PAN; Yang CHANGWEI; Xu JIE (Tehran University of Medical Sciences, 2019)
Background: To identify serum nonylphenol (NP) and glucolipid metabolism-related proteins in Type 2 diabetes (T2D) patients. Methods: We performed a hospital-based, case-control study in patients admitted to the Department of Endocrinology, Hospital of Zunyi Medical University, Zunyi City, China from Mar to Nov of 2014. The study included 112 T2D cases diagnosed in accordance with the 2013 WHO Expert Committee Diabetes Diagnosing Criteria, and 125 healthy individuals with normal fasting blood glucose (FBG) when receiving physical examination in the same period in the Municipal Physical Examination Center. Blood samples from subjects in the 2 groups underwent detection of biochemical indices, including FBG, blood fat, and NP. Glucolipid metabolism-related proteins, including estrogen receptor (ER), sterol regulatory element-binding protein-1c (SREBP-1c), wingless-type MMTV integration site family member 5a (Wnt5a), and peroxisome proliferator-activated receptor-γ (PPAR-γ). These indices were compared between the 2 groups to analyze the correlation between serum NP levels and glucolipid metabolic proteins. Results: The subjects in the diabetes group had higher triglycerides (TG), total cholesterol (TC), NP, ER, SREBP-1c, Wnt5a, FBG, and TG levels than the healthy group, but lower levels of low-density lipoprotein cholesterol (LDL-C) and PPAR-γ than the healthy group. No significant differences in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were found between the two groups. The serum NP levels were shown to be positively correlated with SREBP-1c but negatively correlated with PPAR-γ. Conclusion: The serum NP levels of T2D patients is higher than the levels in healthy controls, and its levels correlate with SREBP-1c and PPAR-γ levels.